Three-body photodisintegration of ⁴He nucleus by linearly polarized photons - Peretiatko, A.A.; Murtazin, R.T.; Khodyachikh, A.F. (Вопросы атомной науки и техники, 2019)
Experimental data are reported from studies of the reaction ⁴He(γ, pn)d through the use of the streamer chamber placed in the magnetic ﬁeld and exposed to a linearly polarized photon beam from the electron linac LUE-2000. A structure has been revealed in the momentum distribution of deuterons. Studies were made into the eﬀects of nucleon-deuteron correlation. The azimuthal distribution of reaction products and the asymmetry of proton production cross-section were measured. The obtained data were analyzed in the framework of the quasideuteron model.